Is Learning English at an Earlier Age Better for Indonesians? - Muhammad Aminullah Hakiki; Laely Hidayati (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2017)
In Indonesia, there exist many native languages which therefore position English as a foreign language following Bahasa Indonesia as the L2. This leads to the development of simultaneous bilinguals. However, there have been some contradictory opinions on whether learning English at an early age is effective as it can inhibit a child’s L1 and L2 development. This may lead to the phenomenon of subtractive bilingualism resulting in a major dilemma for the government and parents. However, this notion can be debated through the critical period hypothesis. This paper presents a literature review on the age factor of learning English and its implication in Indonesia.